Association Between Living Risk and Healthy Life Years Lost Due to Multimorbidity: Observations From the China Health and Retirement Longitudinal Study - Miao, Xinlei; Chen, Jun; Meng, Wen; Wu, Qiong; Wu, Zhiyuan; Ren, Lin; Cai, Yue; Guo, Xiuhua; Zhang, Xiang; Meng, Qun (Frontiers in Medicine, 2022)
Background: Multimorbidity has an effect on life expectancy, while its effect on healthy life years is unclear. This study aims to investigate the associations between healthy life years lost due to multimorbidity and living risk. Methods: The participants of The China Health and Retirement Longitudinal Study (CHRALS) were assessed at four visits between 2011 (baseline) and 2018. At baseline, 13,949 individuals were administered surveys. A combined score based on seven health-related factors was calculated, and participants were classified into 3 groups based on living risk. We used adjusted Cox regression methods to examine associations between living risk groups and multimorbidity. We estimated healthy life years lost due to multimorbidity using the Sullivan method. Results: A total of 9091 adults aged 45 years or older (mean age of 59.55±9.50 years with one disease, 52.60% female) were analyzed in the CHARLS. The probability of no multimorbidity over seven years decreased from 0.9947 to 0.9697 in the low-risk group, the probability of multimorbidity in low living risk was lower than high living risk, ranging from HR 1.253 (95% CI 0.992–1.581; P=0.058) to 1.431 (1.05–1.949; P=0.023) in sex, and ranging from HR 1.340 (95% CI 1.106–1.623; P=0.003) to 2.002 (1.058–3.787; P=0.033) in area. At 45 years, the healthy life years lost in males was less than 0.27 years compared to females in the low-risk group. Hypertension increased the risk of multimorbidity with an HR of 1.5 (95% CI 1.21-1.91; P<0.001) in males. In urban areas, participants with diabetes had a 3.2 times (95% CI 1.75-5.94, P<.001) higher risk of multimorbidity than participants without diabetes. Conclusions: These findings indicate that a low-risk lifestyle could decrease the loss of healthy life years under multimorbidity. The probability of multimorbidity in females and in urban areas was high. Hypertension was correlated with the hazard risk of multimorbidity.